Delays in the Enforcement of Child Support Orders Among Muslims: an Administrative Perspective in Malaysia and Indonesia - Abdul Ghani, Asiah Aqilah; Ahmad, Md Yazid; Muhd Adnan, Nurul Ilyana; Rusli.S, Ardiansyah; Hayeejehwae, Kaosar (al-'adalah, 2025)
Delayed implementation of child support payments by fathers has become a frequently debated topic in child support disputes across innumerable countries, even when mandated by a court order. This study focused on comparing the enforcement of child support orders between Malaysia and Indonesia. It also examined administrative factors in the respective courts that contribute to delays in executing these orders. It adopted the empirical legal study approach, employing content analysis and legal comparison methodologies. Primary data were collected through observation, interviews, and analysis of both primary and secondary sources. Findings revealed that provisions in Malaysian Law (Section 73) and Indonesia's Law No. 1 Article 41 (1974) assign fathers the responsibility of providing for their children. While the basic obligations are similar, differences emerge in the transfer of responsibility to mothers. In Malaysia, child support orders under Section 79 remain effective until the child reaches 18 years. In contrast, in Indonesia, Article 156 (d) of the Compilation of Islamic Law (KHI), consolidated by Article 98 (1), extends this to 21 years. Key factors contributing to delays in child support payments in the Federal Territory Syariah Court, Kuala Lumpur, and the Religious Court of Riau were identified. Both courts faced challenges stemming from a lack of legal awareness among the public and administrative weaknesses, including delays in case hearings. Cumbersome procedures, lengthy processes, and high costs characterized the Religious Court of Riau. Delays in issuing and executing maintenance orders were further exacerbated in the Syariah Court due to insufficient evidence presented by clients